The five key types of Marsilea crenata as a potential identification tool for biology students - W. Wisanti; Siti Zubaidah; Sri Rahayu Lestari; Novita Kartika Indah; Eva Kristinawati Putri (JPBI (Jurnal Pendidikan Biologi Indonesia), 2023)
An identification key is one of the tools used to determine the identity of a plant specimen. This research aims to design an identification key for M. crenata and analyze its potential as an identification tool. The research uses an observational descriptive method. The identification keys were designed for populations growing in aquatic floating, emergent, and terrestrial habitats. The key types designed are (1) short parallel, (2) long parallel, (3) numerical, (4) circular diagram, and (5) columnar diagram. The key characters are qualitative and quantitative, consisting of seven morphological and two anatomical characters. The potential of the identification keys was evaluated based on expert judgment regarding the quality and relevance of the keys as identification tools, accuracy, time, and assessment of student satisfaction. The data were analyzed quantitatively and descriptively. The reliability of expert judgment data was determined based on the percentage of agreement and Cronbach α, while the Kruskal Wallis and Mann-Whitney tests were used to analyze student assessment data and to determine the mean as well as SD of identification time. Student responses were processed in the form of percentages. The results of the expert assessment show that five key types have potential as a tool of identifying ferns diversity. Based on the effectiveness of key use and student assessment, numerical keys are the type that has the least potential, while short parallel keys have the best potential as a tool of identification. However, the five key types that have been developed can be used in learning to train students' identification skills.